Revisiting Cloud Security Threats: Man-in-the-Middle Attack - Singh, Vaishali; Bhatia, Kavita; Pandey, SK (International Journal of Computer Sciences and Engineering, 2019)
Cloud Technology is an emerging technology that has improved the performance of many organizations by utilizing minimum resources and maximum outcomes. Cloud provides virtualized services, applications and can store a large amount of data from various locations. As the cloud environment is accessed through Internet, it cannot be trusted blindly. Thus security is considered as major barrier for users to adopt Cloud, where threats are considered as the major reason for the degradation of the quality of services. For effective use of cloud services, individual focus on the cloud threats is required and an approach is needed from the end user side to gain knowledge about various threats pertaining inside a cloud infrastructure. In the cloud deployment process, various network protocols are used to establish the connectivity between the infrastructure, services and clients. As a result, the server-end needs to be enough strong to provide security to network transmission. However, still the invader secretly accesses the transaction and modifies the communication between two parties. This invader gives birth to most common and critical Man-in-the-Middle (MiTM) attack. The aim of the paper is to re-examine „Man-in-the-Middle‟ attack and its root causes. The focus is to present a broad indication on „Man-in-the-Middle‟ attack, rising as an imperative security concern in cloud computing. The research study aims to review the previous literature and to emphasis on conclusive findings for future research in the related domain based on the published work and industry/organization reports.